Palliative Treatment of Intractable Hematuria in Context of Advanced Bladder Cancer: A Systematic Review - Ghahestani, Seyed Mohammad; Shakhssalim, Nasser (Urology Journal, 2009)
Introduction: In a patient with bladder urothelial cancer that is not suitable for or does not choose curative treatment, intractable hematuria is a disastrous condition. In this article, we tried to review the literature and extract a stepwise approach for palliative treatment of hematuria in these patients. Materials and Methods: The MEDLINE was searched with the help of the Medical Subject Headings system using different combinations of terms urinary bladder neoplasm, hematuria, carboprost, cyclophosphamide, cystitis, alum, and hyperbaric oxygenation. The articles were separately reviewed by the two authors and verified by each other. Eventually, a decision tree was developed for management of gross hematuria in patients with bladder cancer. Results: Although, there was not any reported randomized controlled trial or prospectively designed study, the available case series were rather expressive to draw out a logical approach. Formalin has a grave adverse effect profile and recommended only in special circumstances. For management of each case of gross hematuria in bladder cancer, the etiology of bleeding is the most important determinant. Conclusion: Hematuria in the context of advanced bladder neoplasms can now be effectively treated with fewer side effects using all available modalities in a logical holistic approach. We proposed a decision tree for management of hematuria in this context. However, regarding lack of well-designed trials, a treatment method should be based on individualized scenarios and clinical experience, bringing into account the patient’s preferences.